The Resilience of Rice Imports in Indonesia Against Rupiah Exchange Rate Fluctuations - Jazilah, Nawal (Politeknik Siber Cerdika Internasional, 2026)
Background: Fluctuations in the rupiah exchange rate have the potential to impact the stability of rice imports and national food security in Indonesia. Several studies have examined the influence of exchange rates, import policies, and domestic production on rice imports, but studies examining this issue from an import resilience perspective are still limited. Objectives: This study aims to analyze the resilience of Indonesian rice imports to rupiah exchange rate fluctuations within the framework of national food security. Method: The method used was a literature review of scientific articles and official documents for the 2018–2024 period with thematic analysis. Results: The results show that rice import resilience is not only determined by exchange rate stability, but also influenced by government policies, stock management, and domestic production capacity. Implications: The novelty of this research lies in the integration of the import resilience perspective with exchange rate analysis and food policy to provide a more comprehensive understanding of import-based food resilience in Indonesia.